Genetic and Functional Characterization of Novel Brown-Like Adipocytes Around the Lamprey Brain - Xu, XiaoLuan; Ma, AnQi; Li, TieSong; Cui, WenXue; Wang, XueFeng; Li, Jun; Li, Qingwei; Pang, Yue (Frontiers in Cell and Developmental Biology, 2021)
Many heat-generating organs or mechanisms have appeared throughout the evolution of vertebrates. Mammalian brown adipose tissue (BAT) burns fatty acids to produce heat by uncoupling oxidative phosphorylation from adenosine triphosphate (ATP) production in mitochondria, acting as a natural defense system against hypothermia in mammals and protecting against the development of obesity. Although the existence, cellular origin and molecular identity of BAT in humans have been well studied, the genetic and functional characteristics of brown adipose tissue from lampreys remain unknown. Here, we identified and characterized a novel, naturally existing brown fat depot at the lamprey brain periphery. Similar to human BAT, the lamprey brain periphery contains brown adipose cells that maintain the same morphology as human brown adipocytes, containing multilocular lipid droplets and high mitochondrion numbers. Furthermore, we found that brown adipose cells in the periphery of lamprey brains responded to thermogenic reagent treatment and cold exposure and that lamprey UCP2 promoted precursor adipocyte differentiation. molecular profiling by RNA sequencing revealed repressed inflammation in BAT in normal lampreys relative to lampreys subjected to LPS and 25HC treatment. The results of this study provide new evidence for human BAT research and demonstrate the multilocular adipose cell functions of lampreys, including 1) providing material energy and protecting structure, 2) generating additional heat and contributing to adaptation to low-temperature environments, and 3) resisting external pathogens.